Study of the Effect of Pseudomonas Putida and Funneliformis Mosseae on the Growth and Productivity of Tomato (Solanum Lycopersicum L.) in Senegal - Demba, Diaw; Ndiogou, Gueye; Carras, Sare Idy; Adiouma, Dangue; Abdoulaye, Diop Tahir (European Scientific Journal, ESJ, 2019)
In Senegal, the Niayes zone plays an important role in the economy of the country. It is the main horticultural production area. Among the crops cultivated, tomato (Solanum lycopersicum L.) is the second place of horticultural crops. However, this crop is confronted with biotic and abiotic constraints leading to lower yields. Thus, the objective of this study is to evaluate the impact of beneficial microorganisms such as rhizobacteria from the group of fluorescent Pseudomonas (Pseudomonas putida) and arbuscular mycorrhizal fungi (Funeliformis mosseae) on the productivity of tomatoes. Soil samples were taken from the rhizosphere of tomato plants. The bacterial strains were isolated by the method of suspensions dilutions, and then seeded on King B medium. Their identification was carried out by using the MALDITOF mass spectrometer. In order to evaluate the effect of these microorganisms on productivity, an experiment was conducted in the field for three months. An experimental device with three randomize blocks was adopted with four block treatments: T (control), PS1 (Pseudomonas putida), Fm (Funneliformis mosseae) and PS1 + Fm. The results obtained showed that the inoculation of tomato plants with PS1 or in combination with Fm induced the best yields with values exceeding respectively 5 t / ha and 1.5 t / ha compared with non-inoculated plants. The yield reductions observed in the case of co-inoculation between Fm and PS1 compared with PS1 treatment alone would suggest an antagonistic effect. These strains of Pseudomonas putida constitute an alternative for the increase of tomato productivity in the Niayes zone.